Do Unions and Works Councils Really Dampen the Gender Pay Gap? Discordant Evidence from Germany - Michael Oberfichtner; Claus Schnabel; Marina Töpfer (Institute of Labor Economics (IZA), 2020)
Using a large employer-employee dataset, we provide new evidence on the relationship between the gender pay gap and industrial relations from within German workplaces. Controlling for unobserved workplace heterogeneity, we find no evidence that introducing or abandoning collective agreements or works councils affects the gender pay gap. This result holds at the mean and along the distribution, challenging the stylized fact that unions and works councils dampen the gender pay gap.
Keywords: J31; J50; 330; gender pay gap; industrial relations; works council; collective bargaining; Germany